Polish–English bilingual children overuse referential markers: MLU inflation in Polish-language narratives. Issue 2 (April 2022) - Otwinowska, Agnieszka; Opacki, Marcin; Mieszkowska, Karolina; Białecka-Pikul, Marta; Wodniecka, Zofia; Haman, Ewa
Polish and English differ in the surface realization of the underlying Determiner Phrase (DP): Polish lacks an article system, whereas English makes use of articles for both grammatical and pragmatic reasons. This difference has an impact on how referentiality is rendered in both languages. In this article, the authors investigate the use of referential markers by Polish–English bilingual children and Polish monolingual children. Using the LITMUS-MAIN picture stories, the authors collected speech samples of Polish–English bilinguals raised in the UK ( n = 92, mean age 5;7) and compared them with matched Polish monolinguals ( n = 92, mean age 5;7). The analyses revealed that the bilinguals' mean length of utterance (MLU) in Polish was significantly higher than that of the monolinguals because the bilinguals produced significantly more referential markers (especially pronouns) which inflated their MLU. The authors posit that the non-standard referentiality used by the bilinguals in Polish is caused by cross-language transfer at the syntax–pragmatics interface. When producing narratives in Polish, Polish–English bilinguals overuse referential markers as cohesive devices in their stories, which is not ungrammatical, but pragmatically odd in Polish. Bilinguals tend to do this because they are immersed in English-language input, rich in overt pronouns. Thus, in the process of realizing the surface features of the Polish DP they partly rely on an underlying English DP structure.